2004
DOI: 10.1086/374607
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Measles Viruses Isolated in the United States between 1989 and 2001: Absence of an Endemic Genotype since 1994

Abstract: This report describes measles virus surveillance in the United States for 1989-2001. During the resurgence of measles in the United States between 1989 and 1992, only viruses of genotype D3 were isolated. In contrast, virological surveillance conducted after the resurgence period showed that at least 12 different genotypes were associated with the greatly reduced number of measles cases. Eight different genotypes were identified for 27 chains of transmission in which the source of infection was unknown. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 41 publications
(64 reference statements)
1
39
0
1
Order By: Relevance
“…As with other countries where measles has been eliminated, importations have been found to reflect travel destinations rather than global measles incidence. 30 In the context of steadily increasing short term international departures from NSW during the reporting period, which reached the highest on record in 2011, 31 the current targeting of this group with communication interventions by health authorities would appear relevant. The median age of imported measles cases indicates that international travellers of school age should also be targeted, as evidenced by the outbreaks among school groups returning from overseas trips and in schools subsequent to student travel to affected areas.…”
Section: Discussionmentioning
confidence: 99%
“…As with other countries where measles has been eliminated, importations have been found to reflect travel destinations rather than global measles incidence. 30 In the context of steadily increasing short term international departures from NSW during the reporting period, which reached the highest on record in 2011, 31 the current targeting of this group with communication interventions by health authorities would appear relevant. The median age of imported measles cases indicates that international travellers of school age should also be targeted, as evidenced by the outbreaks among school groups returning from overseas trips and in schools subsequent to student travel to affected areas.…”
Section: Discussionmentioning
confidence: 99%
“…The resurgence of measles in 1989 was preceded by several years during which the incidence of measles was low, and the years after the re- surgence were remarkable for the record low numbers of measles cases reported. This unique epidemiologic situation, together with the ongoing surveillance for cases of measles and the determination of the genotype involved in the epidemic (genotype D3), was critical in the calculation of a revised estimate of the risk of SSPE [23,40,41]. The higher estimated risk of SSPE reported in the present study, compared with the previously estimated risk, could be the result of the different methods used to identify SSPE cases, the underreporting of measles cases during 1989-1991, the higher incidence of measles during the period of resurgence of measles in the population at greatest risk for SSPE (i.e., children !5 years age), or the observation that viruses of genotype D3 are more likely to cause SSPE.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the measles epidemic that occurred in the United States, additional measures were implemented to eliminate the transmission of measles, including the adoption of a 2-dose schedule of measles vaccine administration. As a result, only 312 cases of measles were reported, and measles virus of genotype D3 has not been isolated from individuals whose infection was classified as an indigenous measles case in the United States since March 1992 [22,23]. In 2000, a panel of experts examined measles surveillance data and concluded that elimination of endemic measles in the United States had been achieved [24].…”
mentioning
confidence: 99%
“…The results of the genotyping data in this study suggest a limited number of clade D viruses (genotype D4 and D8) are presently circulating in Ireland with no evidence for circulation of the novel G3 described elsewhere in Europe. This is characteristic of endemic transmission of measles virus and contrasts with geographic regions approaching measles elimination, where an endemic virus is absent and the co-circulation of multiple imported genotypes is generally seen [36]. The molecular characterisation of circulating measles viruses is of increasing importance in confirming the absence of endemic infection in Ireland as Europe aims for the elimination of measles by 2015.…”
Section: Discussionmentioning
confidence: 99%